Collaborative Mapping in the Age of Ubiquitous Internet: An Archaeological Perspective - Piraye Hacıgüzeller (Digital Classics Online)
Over the past decade, collaborative mapping projects have become widespread, allowing for and promoting voluntary participation in cartographic processes. A major factor in the increasing popularity of collaborative mapping in recent years has been the developments in digital cartographic media in general and internet mapping in particular. In this paper the aim is to discuss the possibilities of online collaborative mapping in archaeology. Following an overview of collaborative mapping and its current state in today‘s increasingly online and digital world, four potential modes are introduced through which collaborative mapping in archaeology can be carried out: psychogeography, local community involvement, an online archaeology map system and spatial narratives.